Screening instruments for monitoring market power — The Return on Withholding Capacity Index (RWC) - Bataille, Marc; Bodnar, Olivia; Steinmetz, Alexander; Thorwarth, Susanne (Energy economics, 2019)
While markets have been liberalized all over the world, incumbents often still hold a dominant position, e.g. on energy markets. Thus, wholesale electricity markets are subject to market surveillance. Nevertheless, consolidated findings on abusive practices of market power and their cause and effect in these markets are scarce and non-controversial market monitoring practices fail to exist. Right now, the Residual Supply Index (RSI) is the most important instrument for market monitoring. However, a major drawback of this index is its focus on just one specific aspect of market power in wholesale electricity markets whereas different consequences of market power are possible. Hence, markets could be distorted in several ways and we propose the “Return on Withholding Capacity Index” (RWC) as a complementary index to the RSI. The index is a measure of the firms' incentive to withhold capacity. The benefits and practicability of the RWC are shown by an application on data for the German-Austrian electricity wholesale market in 2016. •We evolved strategies to monitor market power in electricity markets.•We derive a new indicator for market monitoring the “Return on Withholding Capacity” Index.•RWC measures the incentive for an abuse of market power by capacity withholding.•We show that our market power index can be calculated with publicly available data at a reasonable cost.•As an example scenario for market monitoring, we calculate the index for the German-Austrian bidding zone in 2016.